Customer Engagement And Customer Experience Analysis Of Customer Loyalty Through Emotional Bonding - Juliana Tiurida Purba; Mesra, B; Elfitra Desy Surya (International Journal of Society and Law, 2024)
This study aims to test and analyze Customer Engagement (X1), Customer Experience (X2), and Customer Loyalty (Y) mediated by Emotional Bond (Z). The population in this study is consumers with 240 samples taken. The research was conducted from April to June 2024. This study uses quantitative data processed using the SEM-PLS analysis model with Smart PLS 3.0. application. The data source uses primary data taken directly from respondents and secondary data obtained from interviews with customers who come to PLN ULP Delitua The results of the study show that Customer Engagement has a positive and significant influence on satisfaction. Customer experience has a positive and insignificant effect on emotional bonding, the emotional bonding has a positive and insignificant effect on customer loyalty. The Customer Engagement and customer experience nt has a positive and significant effect on emotional bonding. Customer engagement and customer experience has a positive and significant influence on customer loyalty through emotional bonding.